2003
DOI: 10.1034/j.1601-0825.2003.02892.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus and intake of drugs metabolized by polymorphic cytochrome P450 enzymes

Abstract: Confounders like sex, age, systemic diseases, drug distribution into the therapeutic classes, and polypharmacy were similar in the two groups; but the OLP patients consumed more drugs metabolized by CYPs with a PM-risk. The results argue for further investigation of associations between OLP, medication intake and the CYP-enzyme metabolic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 61 publications
2
13
1
12
Order By: Relevance
“…The clinical profile of the OLP patients in this study shares many similarities with those reported by other authors, in terms of female predominance (female/male ratio 3.8:1), age of diagnosis (predominantly over 50 years) and the clinical pattern of the lesions (predominance of the reticular form with bilateral distribution) (4,(13)(14)(15).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The clinical profile of the OLP patients in this study shares many similarities with those reported by other authors, in terms of female predominance (female/male ratio 3.8:1), age of diagnosis (predominantly over 50 years) and the clinical pattern of the lesions (predominance of the reticular form with bilateral distribution) (4,(13)(14)(15).…”
Section: Discussionsupporting
confidence: 70%
“…The female predominance reported in the present study was even higher than those found in other studies (4,10,(14)(15)(16), in which the female/male ratio varied from 1.5:1 to 2.1:1. One possible explanation for this difference is that, routinely, more women (64.5%) than men (35.5%) come to our clinic for a diagnosis of some type oral mu- (3,9,17).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Eleven of them had histological confirmation of all cases with distinguish between OLP and OLL [1,11,23,25,[27][28][29][30][31][32][33] and five presented with control group [11,13,24,25,27]. It can be noticed clear difference in reported coexistence of thyroid gland pathosis and OLP between Northern and Central European countries (Finland [11], Czech Republic [28] and Croatia [34]) and Southern Mediterranean countries (Italy [1,26] and Turkey [29]).…”
Section: Discussionmentioning
confidence: 99%